Implementasi Padat Karya Tunai dalam Bantuan Stimulan Perumahan Swadaya untuk Masyarakat Miskin Kabupaten Trenggalek - Tamami, Dita Soffiya; Marseto, Marseto; Nisa, Fauzatul Laily (Peneliti.net, 2023)
This study aims to determine the impact of implementing a cash work-intensive scheme in the implementation of the Self-Help Housing Stimulant Assistance program as an effort to alleviate community poverty in Trenggalek Regency. The method used in this study uses descriptive qualitative research methods. This method is used to get an overview of socio-economic conditions. The approach used in this study combines data collection methods from literature studies, direct observations of villages and interviews with village officials and village communities. The results of the study show that cash-intensive work in the implementation of Self-Help Housing Stimulant Assistance has been implemented with an impact on employment absorption and the fulfillment of the need for livable housing.